The Impact of Capability on Cooperative Performance and Sustainability: A Case Study of West Java Coffee Farmers Cooperatives - Wini Fetia Wardhiani; Tuti Karyani; Iwan Setiawan; Ery Supriyadi Rustidja (Research Collaboration Community (RCC), 2023)
The industrial revolution in the agricultural sector is faced with demographic challenges (ageing), so intelligent technology, artificial intelligence, big data, and augmented reality are strategic choices. The application of information technology has a direct or indirect impact on Indonesia's agricultural sector, so coffee agribusiness cooperatives' information and communication technology (ICT) is also increasingly needed to respond to market demand. Along with the development of automation, physical, cyber systems and IoT, coffee cooperatives need to be ready and adapt to the era of the industrial revolution 4.0 in capturing market demand opportunities, value chains, and the added value of coffee agribusiness. ICT's presence can improve the performance and institutional sustainability of coffee farmers in rural areas, including cooperatives. Performance is a description of the achievement of organizational tasks to realize the goals, objectives, mission and vision of the organization and its business. The performance of the cooperative describes the services provided to its members and the community/farmers as measured by using indicators to see the working mechanism of the organization and its business that has been carried out and to determine the achievement of the objectives obtained. Meanwhile, the ability to innovate is essential, especially the use of ICT, which is deemed necessary to support the performance and sustainability of coffee cooperatives, so that cooperatives can compete, be stable, or survive in the era of increasing free competition. . Quantitative descriptive method with Linear Regression analysis was used to identify the effect of cooperative capability on the performance and sustainability of cooperatives in several coffee cooperatives in West Java. The study's results found that the power of the cooperative did not significantly affect the performance of the Coffee Cooperative. Still, the capability of the cooperative had a positive and significant effect on the sustainability of the Coffee Cooperative. At the same time, the performance of the cooperative has a positive and significant impact on the sustainability of the coffee cooperative. The ability of cooperatives has a positive and significant effect on sustainability mediated by the performance of the Coffee Cooperative in the Industrial Revolution 4.0 era. This study recommends increasing the capabilities of cooperatives in membership, management, and business models to become sustainable cooperatives based on information technology to achieve added value from market-driven coffee products.